2017
DOI: 10.3892/ol.2017.6574
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-coupled 2D LC/MS-MS analysis of CXCR7-transfected papillary thyroid carcinoma cells: A new insight into CXCR7 regulation of papillary thyroid carcinoma progression and identification of potential biomarkers

Abstract: Abstract. Previous studies have demonstrated that C-X-C chemokine receptor type 7 (CXCR7) regulates papillary thyroid carcinoma (PTC) growth and metastasis; however, the molecular mechanisms underlying this regulation remain unclear. In the present study, the protein expression profiles of the PTC cell line GLAG-66 and GLAG-66 cells stably transfected with CXCR7 cDNA were analyzed and compared using isobaric tag for relative and absolute quantification-coupled two-dimensional liquid chromatography-tandem mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Although PTC pathogenesis has previously been reported to be associated with various biological processes (27,28), the underlying molecular mechanisms remain unclear. GO and pathway enrichment analyses of the identified DEGs demonstrated that they were primarily associated with the RNA polymerase II (Pol II) transcription coactivator, and positive regulation of cell proliferation, cell migration and extracellular exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although PTC pathogenesis has previously been reported to be associated with various biological processes (27,28), the underlying molecular mechanisms remain unclear. GO and pathway enrichment analyses of the identified DEGs demonstrated that they were primarily associated with the RNA polymerase II (Pol II) transcription coactivator, and positive regulation of cell proliferation, cell migration and extracellular exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, transgelin-2 expression is strongly upregulated in pancreatic cancer [68,69], colorectal cancer [70,71], lung adenocarcinomas [72], as well as hepatocellular carcinomas [73], uterine cervical squamous cell carcinomas [74], papillary thyroid carcinoma [75], and bladder cancers [76,77], suggesting that transgelin-2 may serve as a new biomarker to predict the progression and prognosis of cancers [13] (Table 2). More specifically, tissue microarray analyses show a positive staining rate for transgelin-2 of 85% in colorectal cancer, 50% in adenomas, and 75% in hepatic metastasis [70].…”
Section: Transgelin-2 As a Biomarker And Target For Cancermentioning
confidence: 99%